RE-DESIGN MEJA PENOMORAN CYLINDER MENGGUNAKAN PENDEKATAN ANTROPOMETRI DI PT. SMI - Haikal Ikhsanuddin; Subchan Asyari (Prodi Teknik Mesin Universitas Yudharta, 2022)
PT. SMI is a manufacturing company located in Surabaya which is engaged in packaging printing using Rotogravure technology where the use of this technology requires a cylinder as the printing material. Before the cylinder manufacturing process is carried out, the cylinder must be numbered first. The workers when doing the numbering often experience complaints in certain body areas such as complaints on the neck, waist, and arms because the cylinder numbering place is considered less ergonomic. This study aims to re-design the cylinder numbering place which is deemed less ergonomic in the hope of reducing the complaints experienced by workers by using an anthropometric approach, namely through data adequacy tests, data diversity tests, determination of BKA and BKB, and calculation of percentiles. Determination of the design dimensions of the numbering table is obtained by doing calculations, namely the eye height in the standing position is 161.1 cm, the elbow-to-hand length is 41 cm, the hand reach is 69.2 cm, and the shoulder-to-elbow length is 69.2 cm. The length of the numbering table itself follows the standard length of the cylinder at PT. SMI is 1400 cm.